Factors Affecting Sustainable Animal Trypanosomosis Control in Parts of Kaduna State, Nigeria. - Hudu Okankhamame Osue (Journal of Agricultural Extension, 2018)
This study examined the factors affecting sustainable trypanosomiasis control in parts of Kaduna State within the sub-humid savannah ecological zone of Nigeria.  Focus group discussions were held with herdsmen and herd owners (n=85). Questionnaire was administered to participants (n=25) and key-informants (n=5) were interviewed. Most respondents (80%) were Fulani by tribe who could read and write Hausa in Arabic text (ajami). Over 70% were permanent residents practicing transhumant animal husbandry. Animal trypanosomiasis (sammorÃ©), liverfluke (anta), worm infestations (helminthiasis or cinwo anta), and foot and mouth disease (cinwo kafa baki) were ranked in decreasing order of important livestock diseases mentioned. A trypanocide (in sachet) identified to be BerenilÂ® was administered by livestock farmers themselves. Many herd owners and some households had lost various numbers of cattle and herds because of animal trypanosomosis.   Tsetse flies (kudan tsando) were said to be very common, yet many could not differentiate it from other haematophagous biting flies. During dry season, when forage and water shortage is imminent, there is migration to southern parts of Nigeria. More awareness and preference for pour-on and aerial spraying were higher than the use of traps, target or screens. Rearing of trypanotolerant breeds and zero grazing was never practised. There was a viable mutual interaction between crop and livestock farmer in exchange of manure and fodder . A private-public partnership in tsetse and animal trypanosomosis control using commercially available trypanocides and insecticide is feasible and should be effectively explored. Any sustainable control strategy envisaged should recognize the level of awareness of the disease and vectors and willingness of grassroots stakeholders to participate and adapt the control methods.